Psychological assessment for the courts : A survey of psychologists - Martin, Mary-Anne (1999)
The literature relevant to legal standards in criminal, family, and civil settings in relation to psychological assessments for the courts is reviewed. Although over the past twenty years, a number of specialised forensic instruments have been developed for use in forensic settings, it appears that they are infrequently used. Surveys of test use patterns reveal that psychological test use in forensic settings is virtually identical to that in clinical settings, despite the different nature of the referral questions. The debate about the use of psychological tests in forensic assessments, and research on the use of tests in these assessments is also discussed. Research into the quality of forensic evaluations and psychological evidence in court was explored. Literature about evaluation practices and the experiences of psychologists within legal settings is also discussed. Australian psychologists who do forensic assessments for the courts were surveyed about their work settings, experience, training, evaluation practices, and experiences of the legal system. Responses were received from 79 participants who worked in institutional and/or private practice settings. In general, psychologists who do forensic work are satisfied with their experiences in court. This suggests that psychological evidence is well accepted by the courts. The implications of unquestioning acceptance of psychological evidence by the courts are discussed. The results revealed a high use of neuropsychological tests (seven of the top ten most frequently used tests) in forensic assessments in comparison to results from studies in USA and UK. These results highlight the need for a focus on neuropsychology in forensic courses. The survey offers a profile of Australian psychologists providing psychological assessments for the courts